La madera en el Bellum Hispaniense - Cortijo Cerezo, M.ª Luisa (Gerión. Revista de Historia Antigua, 2005)
We have collected the references to wood which appear in the Bellum Hispaniense, since we consider it to be absolutely essencial in the life of the men of antiquity, especially in wartimes. We have carried out a deeper study of the direct references to this product (which this work is really about) and we have collected the indirect references classifying them according to four criteria: generic references; weapons army equipment and war machines; other military words and, finally, various references related to wood.